AN ANALYSIS OF STUDENTS’ WRITING ASSIGNMENT OF ANALYTICAL EXPOSITION TEXT - Muhammad Mujtaba Mitra Zuana (JETAL: Journal of English Teaching & Applied Linguistic, 2020)
Writing is not always easy to do. The students face some difficulties in mastering writing skill because they need particular practice to develop their writing skill. The teacher should know the students’ abilities and difficulties toward this skill and one of many ways teacher can do is by analyzing students’ compositions. In this research, they are generic structures and language features of analytical exposition texts. They may make students find some difficulties in analytical exposition texts. This study is descriptive qualitative study and this research is aiming to describe the students’ competence in writing expository text. The researcher is the first instrument and the second instrument for this study is the students’ compositions of analytical exposition texts. To analyze the data, there will be three steps; classification, analysis, and representing to determine whether the students write analytical exposition text with proper generic structures and language features or not. After being analysis, the researcher found that the students could write analytical exposition texts with a good generic structures and language features. However, there are some students who do not compose them properly. For generic structures, some students often do not write review of arguments in thesis and reiteration. And for language features, some of the students often do not apply the diction well. The students are proficient enough in organizing analytical exposition text in term of generic structures and language features. From the analysis, the abilities and difficulties of the students can be identified by the teacher. The teacher should give clear explanation and understanding in teaching analytical exposition text. The teacher had to explain about how to make analytical exposition text deeply in order that the students could comprehend the text well. In addition, the English teacher could give comments to the students’ composition for the better next writing assignments, because they will know about the mistakes that they still made. Keywords: analytical exposition text, generic structures, language features, writing